A Study of the South Indian Tan-wattles - Chaturvedi, M. D. (Indian Forester, 1951)
The cessation of trade relations with South Africa in 1947-48 and consequent stoppage of wattle imports (40,000 tons annually) from that country have led to an unprecedented demand on the home-grown wattles which had attracted little attention in the past. The elaborate technique adopted in recent plantations, raised on the grassy downs in the Nilgiris (Octacamund) and Upper Pain is (Kodaikanal) where about 20,000 acres are available for the cultivation of wattle, requires considerable modification in the light of large scale failures. A detailed study of the various adverse factors inhibiting the growth of wattle revealed that protection against frost and cold desiccating winds has not had the attention it deserves. The invasion of wattle under the shelter provided by the Eucalyptus plantations and its vigorous development in the gaps where they exist in the overwood, suggests the following technique :- (i) Secure shelter for wattle, 3 years in advance, against- ( a) Strong cold winds by raising Eucalyptus all round an area 5 rows 6 feet apart, and, (b) frost by planting Eucalyptus 40 feet apart. (ii) The existing practice of scrapping of 4 feet wide strips 5 feet apart along the contours ( Kodaikanal ) involving prohibitive costs be replaced by seed beds 2 feet diameter, 9 inches deep and 6 feet apart. (iii) Thin to 12 feet espacement at the end of 3 years. 2. The vigorous growth of wattle on abandoned potato and pyrethrum fields renders it practically immune to frost and suggests the cultivation of potatoes as a means of raising wattl in localities where there is demand for land, such as Nilgiris. Managed on a rotation of 10 years, each unit of area will be for a year under potatoes and for 9 years under wattle, which will more than recoup the loss of soil and its fertility. A crop or two of potatoes will not only pay for the subsequent plantation of wattle but also add to our food supply-a fact not to be lost sight of in the context of the existing food situation. While shelter against frost is not indicated, that against wind would be indispensable in most localities. 3. Possibilities of wattle cultivation exist in Travancore-Cochin where about 20,000 acres could easily be made available. In the higher Himalayan latitudes a lower altitude is indicated. Where chir could replace Eucalyptus to provide shelter.